Audiovisual Literacy in Cinematherapy: Narrative Film and Narrative Transportation to Enhance University Students' Exercise Intention - Saif Oscar Subing; Miftakhul Jannah (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2026)
This study explores how audiovisual literacy, particularly through narrative film, functions within cinematherapy interventions to enhance exercise intention among university students. Using a qualitative-quantitative reception study approach with a quasi-experimental one-group pretest-posttest design, fourteen psychology students with low initial exercise intention participated in three weekly film-viewing sessions featuring Brittany Runs a Marathon, Creed, and Eddie the Eagle. The Exercise Intention Scale was administered before and after the intervention. Results showed a significant increase in exercise intention scores, from an average of 33 to 53 (t = 4.876, p < 0.001; Cohen's d = 1.28). Theoretically, these findings are analyzed through the lens of Narrative Transportation Theory, Social Cognitive Theory, and the Theory of Planned Behavior. The integration of these three frameworks reveals that films are not merely entertainment but function as narrative texts that foster emotional engagement, observational learning, and positive shifts in attitudes and perceived behavioral control. This study concludes that cinematherapy, grounded in audiovisual literacy, offers an accessible, affordable, and emotionally resonant strategy for promoting physical activity motivation among youth, particularly within higher education settings.